SWORD2: hierarchical analysis of protein 3D structures. Issue Volume 50:Issue W1(2022) (17th May 2022) - Cretin, Gabriel; Galochkina, Tatiana; Vander Meersche, Yann; de Brevern, Alexandre G; Postic, Guillaume; Gelly, Jean-Christophe
Abstract: Understanding the functions and origins of proteins requires splitting these macromolecules into fragments that could be independent in terms of folding, activity, or evolution. For that purpose, structural domains are the typical level of analysis, but shorter segments, such as subdomains and supersecondary structures, are insightful as well. Here, we propose SWORD2, a web server for exploring how an input protein structure may be decomposed into 'Protein Units' that can be hierarchically assembled to delimit structural domains. For each partitioning solution, the relevance of the identified substructures is estimated through different measures. This multilevel analysis is achieved by integrating our previous work on domain delineation, 'protein peeling' and model quality assessment. We hope that SWORD2 will be useful to biologists searching for key regions in their proteins of interest and to bioinformaticians building datasets of protein structures. The web server is freely available online: https://www.dsimb.inserm.fr/SWORD2 . Graphical Abstract: